Icelandic currency and the impact on tourist spending behaviour in Iceland: An empirical analysis for the period 2012 to 2018 - Margrét Ósk Rannversdóttir 1996-; Thelma Rut Jóhannsdóttir 1996- (2019)
In the last few years overall spending by tourists staying in Iceland has thought to be growing at a slower pace. Evidence from previous studies have concluded that the exchange rate is the single most important factor when determining tourism expenditure. This thesis will analyse the impact of the exchange rate changes on tourist spending behaviour in Iceland while also discussing overall expenditure, categorical expenditure and ethnicities travelling to Iceland between the period 2012 and 2018. Analysis used are univariate and multiple regressions based on monthly data from changes in tourists card transactions and exchange rate. The results don’t support the initial expectations that exchange rate effects tourism expenditure and instead yields that the main determinant of the recent change in spending habits seen, is the result of tourism flows to Iceland.